Maternal solubility test and high performance liquid chromatography of newborns in combination as a better neonatal screening protocol for sickle cell disease - Sharja Phuljhele; K. Ramnani; S. Hiwale; Priyanka Pruthviraj Ramteke (International Journal of Medical Research and Review, 2016)
Introduction: The incidence and prevalence of sickle cell disease in India is high and they are major health problem in India. Neonatal detection and prophylactic management can reduce morbidity and mortality in childhood. A study is therefore planned for analyzing maternal solubility test and HPLC of newborn as effective screening protocol.Material and Method: The infants born of solubility positive mothers were taken for hemoglobin analysis using Biorad Hemoglobin variant by high performance liquid chromatography (HPLC) at birth and the test was repeated at six months of age. Data were analyzed using appropriate statistical method.Results: A total of 100 mothers were positive on solubility test, their infants underwent Hb analysis by high performance liquid chromatography. 74 infants shows normal hemoglobin variants while 19 were heterozygous for Hbs (sickle cell trait) and 7 babies were homozygous for HbS at birth. On follow up at 6 month of age cases were reanalyzed by HPLC , 12 cases were lost in follow up, 7 cases who were heterozygous for sickle cell turned out to be homozygous for sickle cell, and of those with normal reports 7 cases were homozygous.Conclusion: Maternal solubility test and HPLC of newborn at birth is good screening protocol for sickle cell anemia